What Is a PhD Useful for? - Sarrico, Cláudia (International Higher Education, 2023)
More and more people are getting PhDs. This growth is being driven by government policy, changes in academic work, the demand for doctoral researchers, credentialism, and the import of international talent. There is no longer room in the traditional academic career for all PhD holders. Many become “permadocs,” lingering in an academic precariat; others must transition to jobs outside academia. Doctoral education needs to change to better prepare PhD holders for diverse careers.